Three cases of chronic photodermatitis successfully treated with upadacitinib - Hissa Al-Marri (22827287) (2025)
Photodermatoses represent a varied collection of skin disorders characterized by cutaneous reactions provoked by exposure to ultraviolet radiation. The disease mechanism is based on an immune-mediated delayed hypersensitivity reaction. Clinical presentation of patients with photodermatosis includes pigmentary changes, erythema and/or lichenification, with interindividual differences in lesion morphology and distribution. Most patients report associated symptoms of burning sensation and itchiness as their chief complaint, severely affecting their quality of life. Management of photodermatoses involves both preventive measures and medical management applying topical steroids and calcineurin inhibitors, or systemic immunosuppressives, with variable degree of success and adverse events. Here, we report three cases of chronic photodermatitis treated with upadacitinib, a selective Janus kinase 1 inhibitor, as monotherapy, which resulted in fast, significant and sustainable improvement of signs and symptoms, with a favourable safety and tolerability profile. Other Information Published in: Skin Health and Disease License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1093/skinhd/vzaf049